Heidi Chrisman: capstone - Chrisman, Heidi, artist (Colorado State University. Libraries, 2022)
The artist's statement: My current work focuses on opening the conversation about our bodies and how they work. Personally, I was ignorant to how my body worked until recently. This was because I was not taught about my body as a child and I did not think to ask questions until I was an adult. I did not really know how sex worked until I was 17 and I think there is something wrong with that. I do not want others to have to wonder about things like sex, but be to afraid to ask questions about it. My work aims to make this topic less taboo and to make people less afraid of talking about their bodies. My work features a lot of nude figures and representations of genitalia because I think we need to realize that this is what humans all have in common and we should be able to talk about it just like we do about things like our interests. We all share these experiences with our bodies and our genitalia, but we are embarrassed when someone talks about it. To me, this is wrong. I work in a wide variety of media including, but not limited to: colored pencil, gouache, watercolor, ink, and acrylic paint. I am inspired by many artists, usually nude figure artists and feminist artists. Body positivity is another aspect in my work and the artist Jenny Saville has been influential to me in that area. I have focused more recently on female pleasure in my work, leading me to discover many new feminist artists. I feel strongly that there is not enough attention on pleasure for people with a vulva, sometimes people are almost scared of the clitoris and the vulva as a whole because it can be ‘harder to figure out’. My work is my way to open up the conversation about female pleasure, our bodies, and the problems surrounding these topics. I think it is a tragedy that we do not talk about our bodies and how they work more. The first step to correcting this, is bringing it up.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing